Practical verification strategy for refinement conditions in UML models - García, Diego (2006)
This paper presents an automatic and simple method for creating refinement condition for UML models. Conditions are fully written in OCL, making it unnecessary the application of mathematical languages which are in general hardly accepted to software engineers. Besides, considering that the state space where OCL conditions are evaluated might be too large (or even infinite), the strategy of micromodels is applied in order to reduce the search space. The overall contribution is to propitiate the performing of verification activities during the model-driven development process.